PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BFI FINANCE INDONESIA TBK DIVISI TELEOPERATION CABANG CISAUK KABUPATEN TANGERANG - Sari, Rosita; Andriani, Jeni (Journal of Research and Publication Innovation, 2024)
This study aims to analyze the effect of compensation and work discipline on the performance of PT BFI Finance Indonesia Tbk Divisi Teleoperation cabang cisauk kabupaten tangerang. The research method used in this research is quantitative research. The sample used in this study is the result of the slovin technique, namely 86 respondents. Data analysis used the SPSS version 26 program. The analysis techniques used were data instrument testing, classical assumption testing, analysis testing and hypothesis testing. Testing the hypothesis partially on the compensation variable(X1) obtained the value of tcount > ttable (3,446 > 1,663) and a significancevalue of 0.001 < 0.05. This means that compensation (X1) has a significanteffect on employee performance (Y). Statistical test of work discipline variable (X2) on employee performance obtained tcount > ttable (5,815 > 1,663) and a significant value of 0.000 <0.05. This means that work discipline (X2) has a significant effect on employee performance (Y). Simultaneous hypothesis testing obtained fcount > ftable (124,675 > 3.105) and a significance value of 0,000 < 0,05. So it can be concluded that compensation (X1) and work discipline (X2) have a significant effect simultaneously on employee performance (Y). The determination obtained by R Square is 0.750, meaning that the compensation and work discipline variables together have an influence contribution of 75% on employee performance. While the remaining 25% is influenced by other factors not examined in this study.